PELATIHAN KECERDASAN EMOSIONAL DALAM MENINGKATKAN KEBERHASILAN USAHA UKM - Rodhiah; Thio Lie Sha (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The purpose of this activity is to assist business owners in gaining knowledge about emotional intelligence in entrepreneurship, as it plays a crucial role in enhancing entrepreneurial success. The selected partner for the PKM activity is a recycling business that utilizes large and small used plastic bottles, transforming them into handicraft products such as lampshades, aquariums, flower pots, and more. The business is located in Tangerang, South. This activity is a continuation of a previous PKM initiative and was inspired by the partner's marketing challenges in promoting their recycled products effectively. Initial observations directly with the business owner revealed that the main problem lies in emotional intelligence due to the partners' lack of knowledge in this area, preventing them from achieving business success. The proposed method in this activity involves training and socialization on emotional intelligence, specifically addressing its relevance to offline business success. The aim is to resolve the challenges faced by the recycling business, enabling partners to expand their market reach and marketing areas, with the ultimate goal of achieving greater success in entrepreneurship.